The anticancer potential of various substituted pyridazines and related compounds - Asif, Mohammad (International Journal of Advanced Chemistry, 2014)
Pyridazine nucleus exhibited immense pharmacological activities. Pyridazine nucleus is present in various compounds that possess remarkable pharmacological activities. Various pyridazinone compounds have antitumor activity. Some of them pyridazinone derivatives bearing different moieties were exhibited excellent anticancer activity toward human cancer cell lines. They showed remarkable activity against leukemia, non-small cell lung cancer, colon, central nervous system, melanoma, ovarian and breast cancer cell lines. These compounds were act by different mechanism. Keywords: Pyruvate Kinase; Anti-Cancer; Pyridazines; Biological Activities; Cytotoxicity.